Relationship between Receipt of the Samples of Breast Milk Substitutes in Hospitals and Breastfeeding Practice in Japan - Kaho Hisamatsu; Keiko Nanishi; Midori Matsushima; Sumiyo Okawa; Takahiro Tabuchi (Women's Health Reports)
Objective: This study estimated the percentage of mothers who received samples of breast milk substitutes at medical facilities and examined the relationship between receipt of the samples and breastfeeding practices in Japan. Methods: We used the data from the “The Japan COVID-19 and Society Internet Survey (JACSIS)” conducted in 2021. Two groups of mothers were analyzed: mothers 0–5 months postpartum (n = 1,412) and mothers 5–12 months postpartum (n = 2,045). Logistic regression analysis was conducted with the practice of exclusive breastfeeding as the dependent variable and the receipt of the sample as the explanatory variable. Exclusive breastfeeding was defined in different ways for each group: “exclusive breastfeeding under five months” as measured by 24-hour recall for mothers 0–5 months postpartum, and “exclusive breastfeeding for the first five months” as defined by asking mothers 5–12 months postpartum when they first fed infant formula or baby food and when they finished breastfeeding. Results: The proportion of mothers who received the samples was 82.4%. We found that mothers who received the samples were found to be less likely to continue “exclusive breastfeeding under five months” (odds ratio: 0.71, 95% confidence interval [CI]: 0.51–0.98). In addition, a similar trend was found in a subsample analysis restricted to mothers who intended to breastfeed during pregnancy (odds ratio: 0.62, 95% CI: 0.40–0.94). Conclusions: This study showed that more than 80% of mothers had received the samples of breast milk substitutes, and that receipt of the samples decreased the probability of their practicing exclusive breastfeeding. Regulating distribution of the samples at medical facilities is necessary to prevent interruptions of exclusive breastfeeding.